An unblinkered view of best interests. (5th December 2012) - Martin, Wayne; Freyenhagen, Fabian; Hall, Elizabeth; O'Shea, Tom; Szerletics, Antal; Ashley, Vivienne
Abstract : Wayne Martin and colleagues argue that decisions about patients' best interests must sometimes take into account the interests of others